Perception of teachers towards 'Projek ERaIL' - Shabdin, Ahmad Affendi; Mohamad, Mutiara; Omar, Noor Hafidzah (Universiti Utara Malaysia, 1996)
This study attempts to looks at the perception of teachers towards an in-service training program for primary school teachers in the District of Padang Terap / Pendang Kedah, under a project called 'Project ERaIL ' or English for Rural Learners. The project aims at strengthening the teachers' teaching skill and interest in the teaching of KBSR English. Forty-one teachers were chosen as respondents for the study and five-page questionnaire was designed to provide feedback pertaining to the training. Results show that teachers perceive the project positively and find that the teaching techniques introduced in the training (Oral Interaction, Pairwork, Reading Comprehension, Song, Vocabulary, Dialogue and Blackboard Drawing)are greatly useful in their workplace. Suggested future training topics include Grammar, Public Speaking and Phonetics.